Dukungan Keluarga terhadap Kepatuhan Minum Obat Hipertensi pada Lansia di Wilayah Kerja Puskesmas Muaro Putuih Kecamatan Tanjung Mutiara Kabupaten Agam - Hary Budiman; Hilda Hidayat; Mesi Melinda (Jurnal Riset Hesti Medan, 2022)
Compliance with treatment of patients with hypertension is important because hypertension is a disease that cannot be cured. Hypertension cases at the Muaro Putuih Health Center were 307 cases, only 47 (34.39%) elderly were taking hypertension medication. The purpose of the study was to look at factors related to adherence to taking hypertension medication in the elderly. This type of research is quantitative using a cross-sectional approach. The study was conducted in March 2022 in the working area of the Muaro Putuih Health Center, Tanjung Mutiara District, Agam Regency. The number of samples is 47 using a total sampling technique with inclusion and exclusion criteria. Data processing using a computer application, namely SPSS using the chi-square test is displayed in the form of a distribution table. There is a significant relationship between family support and adherence to taking hypertension medication, the results of the Chi-square P-value statistical test (0.005) < (0.05). It is expected that health workers will form a drug taking supervisor (PMO) in the patient's family to assist all the needs of the elderly in undergoing treatment, monitor and evaluate PMO, provide counseling to families and hypertension patients to provide an understanding of hypertension and build communication with elderly sufferers. hypertension.